Enhancing Well-Being and Resilience in Emerging Adults Through Acceptance Commitment Therapy : A Preventive Group Intervention Study - Nugraha, Fitria; Oriza, Imelda Ika Dian (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study explored the effectiveness of Acceptance and Commitment Therapy (ACT) as a preventive intervention to enhance subjective well-being and resilience among emerging adults who have just graduated from high school. The research utilized a within-subject experimental design, comparing measurements from an intervention group of 8 participants, aged 17 to 20, who had recently graduated high school in the Jabodetabek area. Participants were selected based on their low to moderate scores on the Depression Anxiety Stress Scales (DASS).Â The intervention consisted of five offline sessions, which taught skills in mindfulness, cognitive defusion, values clarification, and committed action. Pre-test and post-test analyses using the Wilcoxon Paired Sample Test revealed no significant immediate increase in subjective well-being. However, a follow-up assessment three weeks later showed a significant improvement in subjective well-being, indicating that while initial changes were not significant, the intervention led to sustained improvements over time. In contrast, resilience scores showed no significant differences across pre-test, post-test, and follow-up measurements. These findings suggest that while ACT appears to be a promising intervention for improving subjective well-being in emerging adults, its impact on resilience may require further investigation. Future studies should consider exploring the effects of extended ACT interventions on resilience and the potential of incorporating additional methods to better capture long-term outcomes.